(untitled) - Farm business management (Illinois, 1992)
This book remains the definitive text on managing a farm or ranch on sound business principles. It was written by the experts as a practical guide for the agribusiness manager. It explains in plain English the principles and techniques that every farmer and rancher must know
Keywords: Agriculture,Nông nghiệp; Economic aspects,Khía cạnh nông nghiệp